EVALUATION OF THE CAUSES AND OUTCOME OF ACUTE ONSET ALTERED SENSORIUM IN ELDERLY PATIENTS ADMITTED IN TERTIARY CARE HOSPITAL - Dr. Abutalha Sheikh; Dr. Yasir Majid; Dr. Aijaz Ahmed Dar; Dr. Khalid Mahmood (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Background: Altered mental status (AMS) is a common clinical presentation with diverse etiologies and significant prognostic implications. Despite its frequent occurrence, the interplay between demographic variables such as age and gender, and clinical outcomes remains underexplored.Objective: This study aimed to evaluate the demographic and clinical predictors of AMS and their impact on hospital outcomes, with a particular focus on age- and gender-related disparities.Methods: This retrospective observational study analyzed 200 patients admitted with AMS to a tertiary care hospital. Demographic data, clinical presentations, Glasgow Coma Scale (GCS) scores, and underlying etiologies were documented. Outcome measures included length of hospital stay, discharge disposition, and in-hospital mortality. Data were statistically analyzed to identify associations between predictors and outcomes.Results: The cohort included 112 males (56%) and 88 females (44%), with a mean age of 62.4 years. Older patients, particularly females, demonstrated significantly worse outcomes, including prolonged hospitalizations and higher mortality rates (p < 0.05). GCS scores at admission emerged as a strong predictor of prognosis, with patients presenting with scores ≤8 experiencing higher mortality (p < 0.001). Infections, metabolic disturbances, and cerebrovascular events were the most common etiologies of AMS, with variations observed across age and gender groups.Conclusion: The study underscores the importance of early recognition and tailored management of AMS, particularly in older and female patients who exhibit poorer outcomes. Early neurological assessment and prompt management of underlying etiologies are crucial for improving prognosis. Further research is warranted to address gender- and age-based disparities and evaluate targeted interventions in this population.